Desain Penelitian Pengembangan Kurikulum Berbasis Pendekatan Saintifik untuk Anak Usia Dini - Khaerani, Anisa; Pratiwi, Dini Putri; Nurunnisa, Fadila; Mashudi, Esya Anesty (Ihya Ulum: Early Childhood Education Journal, 2024)
Early childhood enters a pivotal phase of cognitive and scientific development where love and curiosity are essential. The scientific method is used in the scientific approach in early childhood education to encourage children to observe, ask questions, try, analyse and share the results of their research. This method enhances critical thinking, problem-solving and communication skills. Therefore, the curriculum should be developed with a scientific approach that is appropriate to the nature and developmental needs of early childhood. To develop an innovative and effective curriculum, this study used the research and development method along with the ADDIE model (Analyze, Design, Develop, Implement, and Evaluate). The planning, implementation, and evaluation of the curriculum in Banten are carried out continuously and involve the participation of parents. The results show that the curriculum with a scientific approach is effective in improving early childhood cognitive and science skills. The learning process is designed to allow children to actively participate by observing, questioning, gathering information, reasoning and communicating. This makes learning fun and rewarding. The aim of Banten's curriculum innovation is to improve early childhood education by using contemporary teaching technologies and approaches to meet children's developmental needs.